Predlog Zakona o spremembah in dopolnitvah Zakona o visokem šolstvu – poskus spremembe 8. člena (učni jezik na slovenskih univerzah) - Jesenšek, Marko; Jensterle - Doležalová, Alenka; Potrata, Majda; Božič, Zoran; Žele, Andreja; Komel, Dean; Borovnik, Silvija; Krajnc Ivič, Mira; Žabot, Vlado; Pintarič, Miha; Grad, Silvija (Slavia Centralis, 2020)
MATERIALS: PROPOSED CHANGES AND AMENDMENTS TO THE HIGHER EDUCATION ACT – AN ATTEMPT TO CHANGE ARTICLE 8 (THE LANGUAGE OF INSTRUCTION AT SLOVENIAN UNIVERSITIES)The Rectors Conference of the Republic of Slovenia has proposed some changes to the Higher Education Act, among them a change to Article 8 referring to the language of instruction. The proposed change to this article is problematic, as it allows for Slovenian professors at Slovenian universities to teach classes to Slovenian students in languages other than Slovenian. The Ministry of Education, Science and Sports initiated a public discussion of the proposal and Article 8 has been subject to the most commentary and criticism. Experts began to draw attention to the misguided language policy of those proposing the changes, they also organized a debate in the National Assembly of the Slovenian Parliament, but the proposal was not withdrawn. There has been consistent and strong opposition to the proposed change in the public arena. The Slavic Societies Association of Slovenia initiated a petition for the comprehensive development of the Slovenian language, which was, in a short period of time, signed by over 8.800 people. Such a strong public reaction to a proposed change to the Act has not been seen since the so-called core subjects in the 1980s. At the Education, Science, Sports and Youth Council, the Minister withdrew the controversial Article, claiming that there is no consensus among experts (Comp. website http:// www.zagovor-slovenscine.si/, where all the relevant documents, publications, recordings, statements etc. can be accessed). Public opinion, therefore, has, for the time being, has brought the attempt to Anglicize Slovenian universities to a halt. The present material is a collection of ideas, reservations and reactions of higher-education teachers from Slovenian and international universities (Marko Jesenšek, Alenka Jensterle Doležal, Majda Potrata, Zoran Božič, Andreja Žele, Dean Komel, Silvija Borovnik, Mira Krajnc Ivič, Miha Pintarič). The views expressed by the Slovenian author Vlado Žabot are included as well as the statements by Slovenian institutions (SAZU – Slovenian Academy of Sciences and Arts), institutes (The Institute Nova Revija, the Institute for Humanities), societies (the Slavic societies Association of Slovenia), boards (the program board Toporišičevo leto) and individuals – eminent Slovenian linguists, academicians and others who care about Slovenian as the language of instruction at all levels of education.
Keywords: language of instruction; Slovene language; higher education; internationalization